Bariatric Surgery Impact on Pregnancy and Reproductive Outcomes: A Retrospective Cohort Study in Jordan - Nadia Muhaidat; Satani G Sharkas; Lara Al-Abdallat; Tala Dabit; Tala Basheer Hyasat; Omar Mustafa Odeh Odeh; Ahmad Imad Muhtaseb; Mohammad Rashdan (IMR Press, 2023)
Background: Bariatric surgery is gaining popularity, particularly in women of child-bearing age and its impact on future reproductive potential and pregnancies is indeed an important consideration in a country with a high prevalence of obesity. The aim of this retrospective cohort study is to identify the effect of bariatric surgeries on subsequent pregnancies complications and outcomes, labour and neonatal complications, as well as future fertility. Methods: This study involved a single-center retrospective review of 66 females of reproductive age (18-48 years old) who underwent bariatric surgery in the period of 2014 and 2020, and their pregnancy and reproductive circumstances were compared pre and post surgery. Data was obtained through an online questionnaire filled by data collectors through a phone interview with the participants, in addition to reviewing their past medical records. Statistical analysis was done using SPSS version 20. Results: The results revealed a significant increase in the incidence of low-birthweight infants post bariatric surgery (p = 0.041), compared to the same participants' pregnancies before surgery. In addition, significant decrease in the incidence of gestational diabetes was demonstrated. Women in this study were also less likely to have a miscarriage after the bariatric surgery. Conclusions: Pregnancy following bariatric surgery poses potential challenges regarding reproductive outcomes, despite the positive impact of weight reduction. Further future large scale, multi-center research is required to fully understand the reproductive and obstetric implications of bariatric surgery. Moreover, Patients should receive education on the effect of bariatric surgery on their future pregnancies.